Assessing relative resilience potential of coral reefs to inform management. (December 2015) - Maynard, Jeffrey A.; McKagan, Steven; Raymundo, Laurie; Johnson, Steven; Ahmadia, Gabby N.; Johnston, Lyza; Houk, Peter; Williams, Gareth J.; Kendall, Matt; Heron, Scott F.; van Hooidonk, Ruben; Mcleod, Elizabeth; et al.
ABSTRACT: Ecological resilience assessments are an important part of resilience-based management (RBM) and can help prioritize and target management actions. Use of such assessments has been limited due to a lack of clear guidance on the assessment process. This study builds on the latest scientific advances in RBM to provide that guidance from a resilience assessment undertaken in the Commonwealth of the Northern Mariana Islands (CNMI). We assessed spatial variation in ecological resilience potential at 78 forereef sites near the populated islands of the CNMI: Saipan, Tinian/Aguijan, and Rota. The assessments are based on measuring indicators of resilience processes and are combined with information on anthropogenic stress and larval connectivity. We find great spatial variation in relative resilience potential with many high resilience sites near Saipan (5 of 7) and low resilience sites near Rota (7 of 9). Criteria were developed to identify priority sites for six types of management actions (e.g., conservation, land-based sources of pollution reduction, and fishery management and enforcement) and 51 of the 78 sites met at least one of the sets of criteria. The connectivity simulations developed indicate that Tinian and Aguijan are each roughly 10 × the larvae source that Rota is and twice as frequent a destination. These results may explain the lower relative resilience potential of Rota reefs and indicates that actions in Saipan and Tinian/Aguijan will be important to maintaining supply of larvae. The process we describe for undertaking resilience assessments can be tailored for use in coral reef areas globally and applied to other ecosystems. Highlights: Guidance is presented here for assessing reef resilience to inform management. Field case study from CNMI shows that relative resilience potential can vary greatly. Herbivore biomass and coral recruitment are key resilience drivers in CNMI. Process presented can be applied in all coral reef areas and in other ecosystems. Expanding resilience assessments into vulnerability assessments is key future work.